(untitled) (Research, Society and Development, 2021)
Objective: to understand the processes of co-management, knowledge and practices shared between health professionals and users and their interface with mental health in the network. Methodology: Integrative literature review, which is based on the six phases established by Mendes, Silveira and Galvão, using the PCC strategy for the formulation of the guide question, and detailed and individual search conducted in Scielo, Pubmed and Latin American and Caribbean Literature in Health Sciences (LILACS) via the Virtual Health Library (VHL) in August 2021. Results: 13 articles were selected for analysis and elaboration of the synthesis matrix. Discussion: When addressing the shared management models of health services, one has to consider the limits of any management reform or management model; what can be apprehended based on the articles analyzed, is that for this, it is necessary to consider the most varied and complete factors, being among them, the economic, political, social and cultural context. Conclusion: it is necessary that there is an effort of health professionals and managers to promote co-management in a full way, starting to consider users as a fundamental part for it to be executed, aiming at the construction of space that foster discussions about mental health care in a way shared by all social actors.